Ultraviolet-protective thin film based on PVA–melanin/rod-coated silver nanowires and its application as a transparent capacitor - Albano, Luiz Gustavo Simão [UNESP]; Paulin, João Vitor [UNESP]; Trino, Luciana Daniele [UNESP]; Fernandes, Silvia Leticia; Graeff, Carlos Frederico de Oliveira [UNESP] (Wiley, 2019)
Melanin is a biopigment in many organisms with interesting intrinsic properties suitable for emerging and sustainable technologies. In this work, we report the fabrication of transparent ultraviolet (UV)-protective thin films based on synthetic melanin in poly(vinyl alcohol) (PVA) matrixes. Melanin was synthesized through the auto-oxidation of l-3,4-dihydroxyphenylalanine (l-DOPA) under oxygen pressure, resulting in excellent solubility in water. A thin film with a composition of 3 wt % melanin (synthesized at 6 atm oxygen pressure) and silver nanowires (AgNWs) deposited on the surface has good transparency in visible light and 100% UV irradiation photoprotection. Encapsulated PVA–melanin/AgNW films dipped in water for 7 days retained 98% of their UV irradiation photoprotection. Moreover, using a transparent conductive oxide substrate, this UV-protective system can be simultaneously used as a transparent capacitor. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47805.
Keywords: blends; films; nanoparticles, nanowires, and nanocrystals; optical and photovoltaic applications; surfaces and interfaces